Overexpression of Raf-1 kinase inhibitor protein inhibits cell invasion and migration in lung cancer cells through suppressing epithelial-mesenchymal transition - Wang, Qin; Li, Xin-Ying; Wan, Bing; Zhang, Jie; Sun, Rong; Zhou, Chu-Yao; Zhan, Ping; Song, Yong (Translational Cancer Research, 2019)
Background: Raf-1 kinase inhibitor protein (RKIP) is a small evolutionary conserved protein that was associated with the Raf-MEK-ERK pathway. However, whether RKIP would alter the invasion and metastasis of non-small cell lung cancer (NSCLC) and play the role through suppressing epithelial-mesenchymal transition (EMT) remains to be explored. Methods: A549 cells were transfected with RKIP-GV141 plasmid for overexpression of RKIP. Colony formation assay and MTT assay were performed to measure the effects of RKIP on the proliferation and cell viability assay of A549 cells. Transwell, Migration Assay and wound healing assay were performed to analyze the effects of RKIP on the invasion and metastasis of A549 cells. E-cadherin and vimentin were measured by Western blot to conform RKIP affects invasion and metastasis of NSCLC via inhibiting EMT. Results: RKIP is downregulated in NSCLC tissues compared to adjacent normal lung tissues by IHC. Decreased expression of RKIP contributes to poor prognosis in lung adenocarcinoma patients. Age and pTNM stage were independent prognostic factors for adenocarcinoma patients. Overexpression of RKIP reduces the cell viability and limits the proliferation, invasion, and migration of A549 cells in vitro. Wound healing assay showed the degressive ability of metastasis. High expression of E-cadherin and low expression of vimentin indicated that RKIP affects invasion and metastasis of NSCLC via inhibiting EMT. Conclusions: RKIP is decreased in NSCLC tissues. Overexpression of RKIP in A549 cells would decrease the cellular proliferation, viability, invasion ability, and metastasis ability probably via inhibiting EMT through upregulating E-cadherin expression and downregulating vimentin expression.